The impact of criminal law regulation-based business environment optimization on entrepreneurial spirit and enterprise development - Liu, Xianzhen; Li, Shuai (Frontiers in Psychology, 2022)
The purpose is to explore the impact of the business environment optimization by Criminal Law Regulation (CLR) on Entrepreneurial Spirit (ES) and Enterprise Development (ED) and to provide a reference for subsequent related research. Based on this, this work first makes a detailed analysis of the business environment and CLR. Second, the research hypotheses are put forward, and the conceptual model is proposed. At the same time, a Questionnaire Survey (QS) is designed to analyze the business environment, ES, and ED, and their relationships. Finally, a Structural Equation Model (SEM) is constructed and the CLR-optimized business environment is used as the intermediary variable to explore the impact of the business environment on ES and ED. Then, 200 QSs (recovering 192 valid ones) are distributed to investigate entrepreneurs' attitudes toward ES and ED in different regions. Statistical analysis and independent t-tests are performed on the survey results to judge the relationship between variables. The results of empirical analysis show that (1) The significance coefficient P of ES and ED is 0.005 < 0.01, and the scores of ES and ED of large enterprises are 132.7864 and 142.3243, respectively, which are the highest. Therefore, CLR-optimized business regulation has a significant positive impact on the ED. (2) The influence coefficient of CLR-optimized business regulation and ES is 0.60, and the influence coefficient of CLR-optimized business regulation and ED is 0.75. Therefore, CLR-optimized business regulation plays a positive role in the development of ES. CLR-optimized business regulation plays a regulating role between ES and ED. (3) CLR-optimized business regulation has a significant positive impact on the formation of ES. The policy enlightenment of this work mainly has three points. First, optimizing the business environment can stimulate and protect ES, thus improving the quality of economic growth. All regions should promote “mass entrepreneurship and innovation” and high-quality economic development by improving the convergence of economic policies and building a legal and market-oriented business environment. Second, all regions should implement dynamic and differentiated policies to optimize the business environment's spatial pattern in Chinese cities. Third, there is a need to further strengthen the construction of new infrastructure through cutting-edge information technologies, such as Fifth Generation (5G) mobile communication, Big Data, and Artificial Intelligence (AI).